Transforaminal Epidural Steroid Injection in Lumbar Disc Prolapse: Impact on Pain Intensity and Cognitive Function in Relation to MicroRNA-155 Serum Level - Wael Fathy; Mona Hussein; Rehab Magdy; Mona Nasser; Jehan Mohamed; Doaa Moaz Sayem; Hatem Elmoutaz; Nesma Mounir; Dina Mahmoud Fakhry; Mohamed Abdelbadie (Anesthesiology Research and Practice)
Trial Registration: ClinicalTrials.gov identifier: NCT05626283